Działalność biskupa Polskiego Narodowego Kościoła Katolickiego Józefa Padewskiego w świetle dokumentów zgromadzonych w zasobie Archiwum IPN w latach 1946–1951 - Szłapka, Mateusz (Komunizm: System - Ludzie - Dokumentacja, 2023)
The article aims to show the activities of the bishop of the Polish National Catholic Church, Józef Padewski, as well as the issue of his surveillance and unexplained death. The author, using the materials from the Institute of National Remembrance and the findings of other researchers, primarily tries to present the circumstances of Padewski’s arrest, its causes, and the intervention of the US Embassy. The character of this study is contributory; it is an introduction to broader research both regarding bishop Padewski, as well as the activities of Polish National Catholic Church and the Catholic Church in Poland after the Second World War